2007
DOI: 10.1016/j.econlet.2006.08.029
|View full text |Cite
|
Sign up to set email alerts
|

The wage curve revisited: Estimates from a UK panel

Abstract: Panel data from the United Kingdom are used to estimate a wage curve that allows simultaneously for time, individual, and spatial effects and which thus finesses the problem of grouped data bias. Once allowance is made for the multilevel and crossclassified nature of the data, estimates of the unemployment elasticity of the wage are seen to be volatile and imprecise.JEL Classification: J30

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
(16 reference statements)
2
4
0
1
Order By: Relevance
“…Although not statistically significant, these results are broadly in line with previous studies investigating wage curves for Britain (e.g. Blanchflower and Oswald, 1994a;Black and FitzRoy, 2000;Bell et al, 2002;Johnes, 2007). given the classification chosen.…”
Section: The 'Traditional' Wage Curvesupporting
confidence: 81%
“…Although not statistically significant, these results are broadly in line with previous studies investigating wage curves for Britain (e.g. Blanchflower and Oswald, 1994a;Black and FitzRoy, 2000;Bell et al, 2002;Johnes, 2007). given the classification chosen.…”
Section: The 'Traditional' Wage Curvesupporting
confidence: 81%
“…Moreover, this variable can capture the effects of different productive structures in each region, which probably are insufficiently controlled for by industry sector and occupational dummies. The relative advantages of panel data to crosssectional analysis has been highlighted by Bratsberg and Turunen (1996) and, more recently, by Johnes (2007) in the context of the wage curve literature.…”
Section: Econometric Methodologymentioning
confidence: 99%
“…Studies on the wage curve find the wage curve to be stable around an unemployment elasticity of the wage about −0.1 [32]. However, wage elasticity might differ across regions, as shown in a study conducted by Montuenga et al [33] on five EU countries using information provided by a homogeneous panel data set-the European Community Household Panel on France, Italy, Portugal, Spain, and the UK for the period 1994-96.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Some studies even fail to find a clear negative relationship between wages and unemployment. Pannenberg and Schwarze [35] conducted a study on East Germany for a period from 1992 to 1994 and reported a result that there is no significantly negative relationship between regional wages and regional unemployment for East Germany while Johnes [32] ended up with an unemployment elasticity of the wage for the UK (for a period from 1992 to 2003) that is both volatile and imprecisely determined and a shape that "does not generally accord with any general empirical law" [32, p. 419].…”
Section: Literature Reviewmentioning
confidence: 99%